2014
DOI: 10.1371/journal.pone.0087170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Recurrent STRN/ALK Fusion in Thyroid Carcinomas

Abstract: Thyroid carcinoma is the most common endocrine malignant tumor and accounts for 1% of all new malignant diseases. Among all types and subtypes of thyroid cancers that have been described so far, papillary thyroid carcinoma is the most frequent. The standard management treatment of these tumors consists of surgery, followed by radioiodine treatment in case of high risk of relapse. The most aggressive forms are commonly treated by chemotherapy, radiotherapy or experimental drug testing. We recently reported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 23 publications
6
51
0
3
Order By: Relevance
“…STRN-ALK fusions have been reported most frequently in thyroid carcinoma patients, but were also identified in lung carcinoma and papillary renal cell carcinoma (6,37). Interestingly, similar to this case, thyroid tumors harboring STRN-ALK present with aggressive features, such as extrathyroidal extension and lymph node metastasis (37,38). In this study, seven additional ALK fusion partners were identified, including four novel ALK fusion partners, PPP1R21, SENPF, MAPRE3, and PRKAP1B, which add to the growing list of ALK fusion partners in colorectal carcinoma.…”
Section: Discussionsupporting
confidence: 65%
“…STRN-ALK fusions have been reported most frequently in thyroid carcinoma patients, but were also identified in lung carcinoma and papillary renal cell carcinoma (6,37). Interestingly, similar to this case, thyroid tumors harboring STRN-ALK present with aggressive features, such as extrathyroidal extension and lymph node metastasis (37,38). In this study, seven additional ALK fusion partners were identified, including four novel ALK fusion partners, PPP1R21, SENPF, MAPRE3, and PRKAP1B, which add to the growing list of ALK fusion partners in colorectal carcinoma.…”
Section: Discussionsupporting
confidence: 65%
“…Using CGP conducted during the course of clinical care, this study focused on PAYA cases of papillary, anaplastic, and medullary thyroid carcinoma originating from a variety of practice settings and identified GAs in 93% of these patients. Moreover, most (90%) of the PAYA patients analyzed harbored CRGAs, alterations for which substantial clinical evidence supports an association with response to targeted therapies in various solid tumors, including thyroid carcinomas .…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we identified PAYA patients harboring RET , NTRK1 , NTRK3 , and ALK fusions. Chimeric proteins that pair the RET , NTRK1 , NTRK3 , and ALK kinase domains with dimerization domains have been characterized as oncogenic drivers, identified in a variety of tumor types and shown to confer sensitivity to molecularly targeted therapies . RET and NTRK fusions, though initially identified in PTC as the first kinase fusions in solid tumors, have been more frequently targeted in other tumor types .…”
Section: Discussionmentioning
confidence: 99%
“…The STRN-ALK fusion has been previously reported in thyroid cancer, with an increased frequency in poorly differentiated (9%) and anaplastic thyroid cancer (4%) compared to papillary thyroid cancer (1.6%). 42,43 STRN-ALK fusions have been reported in patients with NSCLC, with a recent case report describing a patient with this rare fusion event and resistance to alectinib. 44 This is the first report of STRN-ALK fusions in a cohort of patients treated with EGFR tyrosine kinase inhibitors (TKIs).…”
Section: Discussionmentioning
confidence: 99%